Rhetorical ideal of a teacher of technical university: essence, content and structure - Zaliubivska, Oksana; Didenko, Alexander (ScienceRise: Pedagogical Education, 2017)
The article describes the modern rhetorical ideal of a teacher of technical university on the base of analysis of rhetorical and pedagogical concepts of ideal and academic eloquence of the prominent representatives of the native higher technical education. Rhetorical ideal of a teacher is defined as historically formed system of requirements to the speech and speech behavior, which embodiment raises the rhetorical pedagogical activity to the perfect level; as a pattern that is a reference point and stimulus for self-perfection in pedagogical rhetorical activity. The content of studied notion is elucidated using binary opposition ‘ideal – anti-ideal” and is structured by the parameters: 1)pedagogical directionality (humanitarian directionality, subordination of technical creativity to the human imperatives against the egocentric and technocratic directionality); 2)the energy of intellect (productivity of scientific thinking (“the culture of open questions”) against stereotype thinking (“the culture of ready answers”); 3) the energy of academic word (correctness, richness, expression, effectiveness of speech, introduction of audience into the searches for truth against the lack of speech culture, artificial pathos, compilation character of learning material); 4) the energy of person (dignity, pedagogical tact in ability to affect, sincerity and nobleness of feelings and words against the vanity, self-confidence; vulgarity of feelings and words); 5) citizenship (fidelity to principles, social activity “ harmony of knowledge and morality” against the unscrupulousness, social indifference, lack of moral responsibility). On the base of analysis of the results of empirical studies the author makes the conclusion that the notions of professional rhetorical ideal are the necessary pedagogical condition of the formation of rhetorical culture in future teachers of technical universities and in first turn, its motivational-value component